Bibliometric Analysis in the Development of Public Sector Digitalization - Windhi Gita Prabawa; Dyah Mutiarin; Eko Priyo Purnomo; Sataporn Roengtam (Universitas Muhammadiyah Yogyakarta, 2024)
Public sector modernization has long been on the political agenda of governments around the world. This study aims to provide an overview of the development of scientific research with the theme of public sector digitalization in the last ten years, from 2014 to 2023. The researcher used the qualitative method with a literature approach. The data source was obtained by accessing journals in the Scopus database with high citation counts. The data obtained was then analyzed using VOSviewer. The results showed that 417 journals studied public sector digitalization from 2014 to 2023. It is widely assumed that the United Kingdom and the United States are the most influential countries in digitalization research in the public sector. The results showed a significant difference in research topics between the UK and the US. Even though this study provides information about public sector digitalization, it has its limitations. The main limitation is that the articles only come from the Scopus database, with no other comparative data. Future research should continue to use data from other databases to contribute more comprehensive knowledge.